RELIABLE AND SECURE HEALTH IOT FOR PATIENT MONITORING WITH BIO-SENSORS IN CLOUD COMPUTING - Maju, Sonam V; V.P, Abeera (IJRDO -Journal of Computer Science Engineering, 2015)
As global ageing and chronic diseases are increasing day by day,we need a revolution from hospitalcentric to home centric. The idea proposed here is an application of Health IoT,where continuous monitoring of oldaged people is done through bio-sensors and non-compliance problem is controlled through a medicine box whichgives alerts through light and sound indicators as medical reminders.The technical era is opting a heartauthentication mechanism and so heart beat signals of a patient have to be secured as well.A reliable and securedmechanism is developed here for the secured heartbeat authentication in the cloud environment.A new cryptographicmethod is developed for security in the cloudsim architecture.